Growth response and yield performance of upland rice intercropped with legumes - Sevirasari, Nindy; Hidayati, Wilujeng; Az Zahroh, Zulfa; Febriansyah, Bayu; Fiana, Marifatul Apri; Rochmaniah, Nabilla Najwa; Faozi, Khavid; Bayyinah, Lafi Na’imatul; Maryanto, Joko; Fauzi, Ahmad (Universitas Padjadjaran, 2026)
Intercropping patterns in upland rice must be carefully managed to prevent excessive competition among crops. This research aimed to determine the ideal proportion of upland rice–legume intercropped and legume types for rice growth and yield. The research was conducted in Mersi, East Purwokerto, Banyumas, Central Java, from April–August 2025. The study was arranged in a split-plot design consisting of a main factor in form of the proportion of upland rice to legumes (1:1, 2:1, and 3:1), and a sub-factor, i.e., legume types (peanuts, mung beans, and soybeans). The data were analyzed using Analysis of Variance and Tukey's HSD test at α = 5%. The results showed that the height of upland rice plants in intercropping was significantly higher than in sole cropping at 35 and 56 days after planting (DAP). The SPAD leaf greenness index of upland rice leaves at 70 DAP in sole cropping was significantly higher than in intercropping. Intercropping produced the insignificant number of stems, leaves, panicles, dry weight, number, and weight of grain per plant as upland rice in sole cropping. The number and weight of empty grains per plant, as well as upland rice productivity in sole cropping, were significantly higher than in intercropping. Both factors did not significantly affect the growth and yield of upland rice under intercropping condition. Intercropping upland rice and peanuts at a 2:1 planting proportion resulted in a land equivalent ratio greater than 1, indicating that the system was productive and efficient despite a high competitive ratio.